Open mini-incision parathyroidectomy under regional anesthesia: Surgical technique and report of the first 8 cases in Nakornping Hospital - Kaewsiri, Kullaboot; Nuglor, Papob (Journal of Nakornping Hospital, 2025)
Introduction: Parathyroidectomy is often required in patients with parathyroid dysfunction or related conditions. From traditionally operation, new and advances in surgical and anesthetic techniques, regional anesthesia has emerged as a potential alternative. Objective: To evaluate surgical outcomes of parathyroidectomy under regional anesthesia, including operative details, surgical success, operative time, intraoperative pain, cost, hospital stay, and postoperative complications. Methods: A retrospective descriptive study was conducted among patients who underwent parathyroidectomy under regional anesthesia in the Department of Otolaryngology, Nakornping Hospital, Chiang Mai, between May 1 and September 1, 2023. Demographic data, surgical parameters, and outcomes were reviewed. Results: Eight patients (6 males, 2 females) underwent the procedure. The mean age was 45.13 ± 13.57 years (range, 29–73), with a mean BMI of 22.21 ± 3.03 kg/m². Indications included end-stage renal disease with hyperparathyroidism (n = 7) and parathyroid adenoma (n = 1). The mean operative time was 108.13 ± 30.30 minutes. The mean operative cost per day was 15,597.50 ± 648.53 THB. Intraoperative pain assessed by the Visual Analog Scale (VAS) was 0 in seven patients (87.5%) and 2 in one patient (12.5%). All seven patients on maintenance hemodialysis continued treatment without interruption. A transient unilateral phrenic nerve block occurred in one case but surgery was completed safely, and the patient recovered fully postoperatively. Conclusion: Parathyroidectomy under regional anesthesia yielded excellent surgical outcomes with minimal intraoperative pain, low complication rates, and reduced anesthetic risks. This approach represents a safe and effective alternative to general anesthesia, particularly in high-risk patients.